A gelatin sponge-hemocoagulase sealant for preventing tumor biopsy complications: a dual mechanical and pharmacological barrier - Chen, Xiangrui; Hu, Min; Du, Lunfei; Hao, Chengluo; Yang, Hui; Han, Yunwei; Liu, Xin (Frontiers in Oncology, 2025)
BackgroundA CT-guided tumor biopsies carry substantial risks, with literature-reported complication rates reaching 43% and pulmonary biopsy pneumothorax intervention rates as high as 22.1%. This study validates a novel needle tract sealing technique combining absorbable gelatin sponge (mechanical occlusion) with Agkistrodon acutus-derived hemocoagulase (local coagulation), leveraging synergistic physico-chemical mechanisms.MethodsThis prospective single-arm cohort enrolled 87 consecutive patients undergoing CT-guided biopsies (Feb 2023-Jun 2025). The core technique involved retrograde injection during needle withdrawal of 1mm³ gelatin sponge particles suspended in 0.5KU hemocoagulase (total volume: 1.5ml), with stratified dosing for D-dimer levels >2mg/L. Primary outcomes were intervention-requiring complications such as symptomatic pneumothorax or clinically significant hemorrhage.ResultsAmong 87 patients (42 pulmonary), the composite technique reduced overall complications to 4.6% (4/87) vs 43% literature rate (p < 0.001). Pulmonary biopsies achieved significantly lower pneumothorax intervention rates (2.38% vs 22.1%, p < 0.001) and subclinical stabilization of 87.9% imaging abnormalities. Organ-specific protection was observed in extrapulmonary biopsies (zero severe complications). D-dimer-stratified dosing reduced hyperfibrinolytic hemorrhage risk by 86.8% (p = 0.001).ConclusionThe gelatin sponge-hemocoagulase composite significantly reduces CT-guided biopsy complications through dual mechanical-coagulation mechanisms, establishing a universally applicable, precision-stratified safety protocol.